Очерки народной жизни - Семанова Мария Леонтьевна (Библиотека русской художественной публицистики, 1986)
Экземпляры: КХ (20110820) / Инвентарный номер: 867580 / Сис.шифр: Р1 / Авт.знак: О-95 / ГРНТИ: 17 / ББК: 84(2=411.2)-4я43